Tandem-L: A Radar Mission Proposal to Capture Earth Dynamics - Eineder, Michael; Hajnsek, Irena; Moreira, Alberto; Bamler, Richard; Krieger, Gerhard; Minet, Christian; De Zan, Francesco (2011)
Tandem-L is a proposal prepared by DLR and NASA for an L-band Synthetic Aperture Radar (SAR) mission to monitor important parameters of four different Earth spheres with different priorities. First priority: 1. Geosphere: the mission shall perform weekly measurements at global geo-risk areas such as volcanoes, plate boundaries and landslide areas. Additionally, areas where anthropogenic surface changes are expected shall be monitored. Examples for the latter are groundwater extraction in cities or carbon capture and storage sites. 2. Biosphere: the mission shall establish inventories of global forest heights and biomass and monitor the changes over 5 years. Second priority: 3. Cryosphere: the mission shall capture sea ice extent, permafrost, glacier and ice cap dynamics. 4. Hydrosphere: the mission shall perform measurements in different disciplines such as soil moisture, flooding and ocean currents. This contribution gives an overview over the mission. The presented goals and requirements will focus on geolocical applications (geosphere).